Analisis Kesiapan Digitalisasi Sistem Akuntansi dalam Pengelolaan Dana BOS pada Lembaga Pendidikan Menengah: Studi Empiris di Kota Padang - Hayati, Dian Indah; Ristapawa Indra (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study aims to analyze the level of readiness for accounting system digitalization in managing the School Operational Assistance (BOS) funds at the senior high school (SMA) level in Padang City. The research employs a descriptive quantitative approach using a survey method. Data were collected through questionnaires distributed to 68 respondents from 17 high schools, comprising school principals, administrative heads, treasurers, and system operators. The research instrument focuses on four main variables: technological infrastructure, human resource (HR) competence, institutional policy support, and digitalization readiness. The results show that most schools already possess adequate infrastructure and competent HR, along with internal policies that support the implementation of digital accounting systems. Overall, the level of digital readiness in managing BOS funds is categorized as good, as reflected by the majority of responses ranging from “agree” to “strongly agree.” Based on these findings, the study recommends enhancing staff training, strengthening institutional policies, and conducting continuous evaluation of digital systems to ensure the effectiveness and sustainability of accounting digitalization in secondary education institutions.